EXtending Omalizumab Treatment Intervals in patients with Chronic spontaneous urticaria (EXOTIC): protocol of a multicentre, randomised, open-label, non-inferiority trial - Alexander Egeberg; Ditte Georgina Zhang; Christian Vestergaard; Simon Francis Thomsen; Jennifer Astrup Sørensen; Misbah Noshela Ghazanfar; Zarqa Ali; Jacob Thyssen (BMJ Open)
Introduction Omalizumab, an anti-IgE monoclonal antibody, is effective in treating antihistamine-refractory chronic spontaneous urticaria (CSU). However, tapering strategies for omalizumab are currently not well-studied, and patients may be treated longer than needed. Here, we present the rationale and design of the EXtending Omalizumab Treatment Intervals in patients with Chronic spontaneous urticaria trial, a multicentre, randomised, open-label, non-inferiority clinical trial. The objective of this trial is to investigate if patients with well-controlled CSU, achieved by standard treatment of 300 mg omalizumab administered subcutaneously every 4 weeks (Q4W) for 12 weeks, can maintain disease control with every 6 weeks (Q6W) dosing interval.Methods and analysis Participants who achieve an Urticaria Control Test (UCT) score ≥12 after 12 weeks on omalizumab will be randomised to 300 mg omalizumab treatment Q4W or Q6W. Treatment arms will be followed for a total of 36 weeks. The primary endpoint is the absolute difference in average UCT score between treatment arms at week 36. Blood samples, Weekly Urticaria Activity Score, Chronic Urticaria Quality of Life Questionnaire, Dermatology Life Quality Index and records of side effects and flares will be obtained throughout the study at weeks 0, 12, 24 and 36.Ethics and dissemination The study has been approved by the Scientific Ethical Committee of the Capital Region in Denmark, the local Data Protection Agency and the Danish Medicines Agency. All study participants must provide written informed consent. The study will be conducted according to the Helsinki Declaration and Good Clinical Practice. Findings will be disseminated through publication in peer-reviewed journals and presented at international conferences.Trial registration number EU CT no. 2023-506187-14-00, ClinicalTrials.gov: NCT05916937.